Crystal structure of N ′-hydroxypyrimidine-2-carboximidamide - Jasmine, Nithianantham Jeeva; Muthiah, Packianathan Thomas; Stanley, Nithianantham (Acta crystallographica. Section E, Structure reports online, 2014)
The title compound, C 5 H 6 N 4 O, is approximately planar, with an angle of 11.04 (15)° between the planes of the pyrimidine ring and the non-H atoms of the carboximidamide unit. The molecule adopts an E configuration about the C=N double bond. In the crystal, adjacent molecules are linked by pairs of N—H...O hydrogen bonds, forming inversion dimers with an R 2 2 (10) ring motif. The dimers are further linked via N—H...N and O—H...N hydrogen bonds into a sheet structure parallel to the ac plane. The crystal structure also features N—H...O and weak C—H...O hydrogen bonds and offset π–π stacking interactions between adjacent pyrimidine rings [centroid–centroid distance = 3.622 (1) Å].